Symmetry and Perturbation Theory (Spt 2001) : SPT 2001 Proceedings of the International Conference Cala Gonone, Sardinia, Italy 6-13 May 2001. - Bambusi, Dario (World Scientific Publishing Company, 2001)
The third conference on "Symmetry and Perturbation Theory" (SPT2001) was attended by over 50 mathematicians, physicists and chemists. The proceedings present the advancement of research in this field - more precisely, in the different fields at whose crossroads symmetry and perturbation theory sit. Contents: Geometry and Dynamics of Hyperelliptically Separable Systems (S Abenda); A Functional Analysis Approach to Arnold Diffusion (M Berti); Linearizing Resonant Normal Forms (G Gaeta); Tori Breakdown in Coupled Map Lattices (C Giberti); A Two-Dimensional Version of the Camassa-Holm Equation (H-